Factores precipitantes del intento suicida en tres habitantes en adultez joven del municipio de Roldanillo (V) (2021)
This research aims to analyze the factors that precipitate suicide attempts in step defined as young adulthood, comprising from 20 to 40 years old, in a group of 3 people of the village of Roldanillo, Valley Cauca having into account, the environment in which they operate, social relationships, biological, psychosocial and personal patterns, which may be influencing or influencing their suicidal thoughts and ideas. The research uses a qualitative approach which begins to develop in a semi-structured interview and on a scale of suicidal ideation in which we can identify the recurrence of suicidal thoughts and place numerous desires, thoughts or wishes to self-harm. Leading to confront the theoretical and practical ideas, research to provide a broader vision and clear of what may be affecting participants. The research allows us to analyze factors that are already evidenced in other studies, such as possible “emerging risks” found in participating young adults, such as psychiatric family history, unemployment, little sense of life and experiences of abuse in childhood and adolescence. Finally, this research seeks to have a place in clinical, social psychology and cause an alert to the health system; to consider that suicide in young adulthood is present, and it is possible to find the root of these thoughts, in order to prevent them and avoid consequences without return.